Mass fatality management concise field guide - Dudley, Mary H. (CRC Press, 2013)
In a mass fatality incident, members of the medical examiner or coroner's office are faced with a host of complex and time-sensitive responsibilities. These include identifying victims, collecting property and evidence, determining cause and manner of death, issuing death certificates, and returning the bodies to their families. Written for all personnel involved in these incidents, Mass Fatality Management Concise Field Guide outlines the necessary components to prepare for and manage mass fatalities